Coronavirus disease 2019 (COVID-19) in the heart transplant population: a single-centre experience. (19th October 2020) - Caraffa, Raphael; Bagozzi, Lorenzo; Fiocco, Alessandro; Bifulco, Olimpia; Nadali, Matteo; Ponzoni, Matteo; Carrozzini, Massimiliano; Toscano, Giuseppe; Fraiese, Angela Pompea; Metra, Marco; Lombardi, Carlo Maria; Serafini, Francesco; et al.
Abstract: OBJECTIVES: Few anecdotal cases have been reported in the literature regarding heart transplant recipients and infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We report our experience with 6 patients hospitalized in Northern Italy during the outbreak. METHODS: Of the 396 living heart transplant recipients from 1985 to 2020 included in the study, 6 patients developed the novel 2019 coronavirus disease. Risk factors, last follow-up characteristics, onset presentation, in-hospital course of disease and blood examinations data were collected for these patients. RESULTS: All patients were symptomatic and had positive results from a nasopharyngeal swab test for SARS-CoV-2. Of the 6 patients, 5 were hospitalized and 1 remained self-quarantined at home. Two patients died and 3 were discharged home. Two patients were admittted to the intensive care unit . Immunosuppressive therapy was modified with a median reduction comprising doses that were 50% cyclosporine and 50% mycophenolate. All patients received a medium-dose of corticosteroids as a bolus medication in addition to their therapy. All hospitalized patients received hydroxychloroquine; 2 patients received ritonavir/lopinavir. Broad-spectrum antibiotics for prophylaxis were administered to all. One patient had an ischaemic stroke and died of sepsis. CONCLUSIONS: In the absence of any strong evidence regarding the treatment of heart transplant recipients infected with SARS-CoV-2, we faced a new challenge in managing viral infection in an immunosuppressed population. Because immunomodulation interaction with the infection seems to be crucial for developing severe forms of the disease, we managed to reduce immunosuppressive therapy by adding medium doses of corticosteroids. Despite the limited number of affected patients, this report suggests that special considerations should be given to treating coronavirus disease in the heart transplant recipient population. Abstract : The worldwide spread of the novel coronavirus disease 2019 (COVID-19) pandemic, first identified in Wuhan, China, has created unprecedented challenges in the diagnosis and medical treatment of affected patients as well as in public health management.